Emergency Action Planning in Collegiate Athletics: An Evaluation of the Current Adoption of Best Practice Recommendations - Kyler Conn; Ken Blood; Genna Fusco (Journal of Sports Medicine and Allied Health Sciences: Official Journal of the Ohio Athletic Trainers' Association)
OBJECTIVE The primary objective of this study was to assess the current adoption of the National Athletic Trainers’ Association’s (NATA) best practice recommendations regarding emergency planning, outlined in the NATA Position Statement: Emergency Planning in Athletics, at the collegiate level.